Gut Health: The New Paradigm in Animal Production? - Ryan J. Arsenault (Frontiers Research Topics, 2016)
Gut health and specifically the gut microbiome-host interaction is currently a major research topic across the life sciences. In the case of animal sciences research into animal production and health, the gut has been a continuous area of interest. Production parameters such as growth and feed efficiency are entirely dependent on optimum gut health. In addition, the gut is a major immune organ and one of the first lines of defense in animal disease. Recent changes in animal production management and feed regulations, both regulatory and consumer driven, have placed added emphasis on finding ways to optimize gut health in novel and effective ways. In this volume we bring together original research and review articles covering three major categories of gut health and animal production: the gut microbiome, mucosal immunology, and feed-based interventions. Included within these categories is a broad range of scientific expertise and experimental approaches that span food animal production. Our goal in bringing together the articles on this research topic is to survey the current knowledge on gut health in animal production. The following 15 articles include knowledge and perspectives from researchers from multiple countries and research perspectives, all with the central goal of improving animal health and production.